Evaluation of certain veterinary drug residues in food : eighty-fifth report ofthe Joint FAO/WHO Expert Committee on Food Additives (World Health Organization, 2018)
This report represents the conclusions of a Joint FAO/WHO Expert Committee convened to evaluate the safety of residues of certain veterinary drugs in food and to recommend maximum levels for such residues in food.
WHO technical report series ; 1008
Keywords: No-Observed-Adverse-Effect Level; zemědělství a potravinářství; Maximum Allowable Concentration; kontaminace potravin; hodnocení rizik; maximální přípustná koncentrace; Veterinary Drugs; rezidua léčiv; farmacie a farmakologie; Drug Residues; dávka bez pozorovaného nepříznivého účinku; veterinární léky; Risk Assessment; Food Contamination